22‐1: Invited Paper: Latest Evolution of Small Molecule Based Emissive Layers for Ink Jet Printed OLED Displays. Issue 1 (28th June 2021) - Stolz, Sebastian; Meyer, Sebastian; Hayer, Anna; Linge, Rouven; Engel, Miriam; Rodríguez, Lara-Isabel; Hamburger, Manuel; Tseng, Hsin-Rong; Jatsch, Anja; Anémian, Rémi
Abstract : This article reviews the current performance of inkjet printed OLEDs. Recent progress on the crucial parameter of blue sub‐pixel lifetime is shown, achieved by improving the stability of the emissive material. By adjusting the charge balance towards highest efficiency, an external quantum efficiency of 11% can be achieved. Further progress on efficiency is also illustrated for red devices. Within latest R&D type material, a significant efficiency increase can be observed by an improvement of the horizontal orientation of the emissive material. Prospectively, this will close the gap between evaporated and printed red devices.